Bibliometric analysis of research trends in agricultural soil organic carbon components from 2000 to 2023 - Ge, Guolong; Chen, Xuanyi; Ma, Hexiao; Zhang, Xiangqian; Shi, Jingjing; Wang, Xiaoxiang; Zhao, Xiaoqing; Wang, Manxiu; Xian, Feng; Lu, Zhanyuan; Cheng, Yuchen (Frontiers in Plant Science, 2024)
In recent years, considerable research has focused on the interactions between soil organic carbon components and their responses to varied land use and agricultural practices. However, the mechanism of soil organic carbon sequestration and response characteristics of soil organic carbon components to soil carbon pools are still subject to some debate. To the best of our knowledge, no researchers have used bibliometric analyses to explore the field of soil organic carbon components. This study thus involved the use of bibliometric techniques to identify research hotspots in the study of organic carbon components over the last 23 years and future trends in research development. Specifically, a comprehensive literature review of 607 documents pertaining to organic carbon components was performed using the Web of Science database, covering the period from 2000 to 2023. Employing CiteSpace, we visualized and analyzed the data across national, institutional, disciplinary and keyword dimensions.The results indicate that researchers in the United States and China have substantially influenced the study of soil organic carbon components. Since 2000, the United States has pioneered the study of soil organic carbon components, establishing a foundational role in this field of research. Meanwhile, China leads with the largest number of publications and most diverse research directions in this field. Among the institutions involved in such research, the University of Chinese Academy of Sciences has the highest number of publications. The investigation of soil organic carbon components within agricultural systems is inherently multidisciplinary, with the most comprehensive research being performed within the soil sciences discipline. At present, the focal areas of research on soil organic carbon components predominantly revolve around the impacts of straw return to fields, varying land-use changes, restoration of vegetation and the reciprocal effects of soil organic carbon components on the restoration of vegetation. The findings of this work highlight the research hotspots within the field of soil organic carbon components and the emerging trends within this field. This work offers novel insights into the dynamics of soil organic carbon components, potentially guiding future studies in this vital field.